EVALUASI WASTE PADA PROYEK GEDUNG DI WILAYAH SEMARANG - Hanintyo Hadiman; Jati Utomo Dwi Hatmoko; Frida Kistiani (Jurnal Karya Teknik Sipil, 2014)
Construction project have problems regarding waste, which can be in forms of Physical Construction Waste and Non-Value Adding Activity. The purpose of this research is to evaluate waste that occured in construction projects, while the aim of this research is to know the frequency and impact of waste, as well as the waste cause factor. The object of the research was waste on building project in the area of Semarang. Waste identification was carried outfrom literature, observation and interview and wereanalyzed using fishbone diagram to get waste cause factor variable. Waste variables were divided into four categories, i.e. waiting periods, material, human resources, and operations. Waste cause factor variables were grouped into six categories, i.e. people, professional management, design and documentation, materials, execution and external.Questionnaires were distributed to 100 respondents of 12 different contractors, with response rate of 65%. Data was processed by Weighted Mean Score (WMS) method. The results of this research showed that “extra work” waste had the highest frequency, “rework and repair” waste had the highest impact, and “slow drawing revision and distribution” and “design changes”, were the highest waste cause factors on building projects in the area of Semarang. The results of data processing also showed that structural works was type of work where waste often occurred. The result of risk-waste matrix showed that “extra work” was included into high risk-waste category which means it could cause serious disruptions to the project execution and company’s finance.